2013
DOI: 10.1371/journal.pone.0061957
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Molecular Epidemiology and Evolutionary Dynamics of Influenza A Virus in Taiwan

Abstract: The evolution and population dynamics of human influenza in Taiwan is a microcosm of the viruses circulating worldwide, which has not yet been studied in detail. We collected 343 representative full genome sequences of human influenza A viruses isolated in Taiwan between 1979 and 2009. Phylogenetic and antigenic data analysis revealed that H1N1 and H3N2 viruses consistently co-circulated in Taiwan, although they were characterized by different temporal dynamics and degrees of genetic diversity. Moreover, influ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 45 publications
0
11
0
Order By: Relevance
“…28 These results demonstrate that the vaccine strains recommended by the WHO were circulating in Taiwan one to two influenza seasons earlier. The seasonal patterns synchronized with genetic diversity of influenza B viruses observed in Taiwan make it possible to capture the evolutionary dynamics and epidemiological rules governing antigenic drift 29 and may serve as an early warning system for the detection of an emerging new epidemic strain.…”
Section: Discussionmentioning
confidence: 99%
“…28 These results demonstrate that the vaccine strains recommended by the WHO were circulating in Taiwan one to two influenza seasons earlier. The seasonal patterns synchronized with genetic diversity of influenza B viruses observed in Taiwan make it possible to capture the evolutionary dynamics and epidemiological rules governing antigenic drift 29 and may serve as an early warning system for the detection of an emerging new epidemic strain.…”
Section: Discussionmentioning
confidence: 99%
“…The expression level of NP and β-actin were examined by Western blot and analyzed by Quantity One software from the dominant strain of previous season. Analysis of the human H3N2 whole genome sequences from databases revealed that there are evolutions in codon usage and frequent reassortment events [35][36][37]. A Previous study showed that reassortment occurred whereby A/ Sydney/5/97 converted to A/Fujian/411/02 strain, and A/Fujian/411/02 converted to A/California/7/04 strain [37].…”
Section: Discussionmentioning
confidence: 99%
“…Five influenza seasons were dominated by H1N1, which were preceded by H3N2 during the most recent 5 years. In addition, H3N2 viruses frequently cocirculated with influenza B viruses in several seasons (2000-01, 2004-05, and 2006-07 seasons) [ 8 ]. This illustrates that the influenza A viruses were somewhat more active in Taiwan.…”
Section: Influenza Epidemics and Pandemicsmentioning
confidence: 99%
“…Influenza A virus is one of the most active pathogens in Taiwan causing regular, yearly islandwide epidemics and associated with significant morbidity and mortality in humans [ 7 , 8 ]. Influenza subtypes H1N1 and H3N2 are currently the major circulating subtypes and have been infecting the human population for several decades.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation